2018
DOI: 10.1371/journal.pone.0205421
|View full text |Cite
|
Sign up to set email alerts
|

Marker-trait associations in two-rowed spring barley accessions from Kazakhstan and the USA

Abstract: In this study, phenotyping and single nucleotide polymorphism (SNP) genotyping data of 272 accessions of two-rowed spring barley from the USA along with 94 accessions from Kazakhstan were assessed in field trials at six breeding organizations in Kazakhstan to evaluate the performance of the USA samples over three years (2009–2011). The average grain yield over the six locations was not significantly higher in Kazakh accessions in comparison to the USA samples. Twenty four samples from Montana, Washington, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 55 publications
3
15
1
Order By: Relevance
“…One QTL with pleotropic effects located at 91,078,604 bp on chromosome 1H was associated with all three traits in four trials. A QTL at 766,144,076 bp on chromosome 2H was related to the three traits HD_LS, PH_NM, and SL_NC, and was also associated with PH, days to seed maturation (SMT), peduncle length (PL), and HD, as reported by Genievskaya et al ( 2018 ). Of 28 pleotropic-effect QTLs, six were detected by EigenGWAS as well, and these are shown in red text highlighted in yellow in Figures 3A–C and Table 2 .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…One QTL with pleotropic effects located at 91,078,604 bp on chromosome 1H was associated with all three traits in four trials. A QTL at 766,144,076 bp on chromosome 2H was related to the three traits HD_LS, PH_NM, and SL_NC, and was also associated with PH, days to seed maturation (SMT), peduncle length (PL), and HD, as reported by Genievskaya et al ( 2018 ). Of 28 pleotropic-effect QTLs, six were detected by EigenGWAS as well, and these are shown in red text highlighted in yellow in Figures 3A–C and Table 2 .…”
Section: Resultssupporting
confidence: 63%
“…At present, the genetic architecture of grain starch quality (Li et al, 2014 ) and drought stress tolerance (Zeng et al, 2016 ) has been studied in qingke barley, and salt and aluminum tolerance have been studied in Tibetan wild barley (Qiu et al, 2011 ; Wu et al, 2011 ; Cai et al, 2013 ). In other studies, diverse barley lines from different regions, including the US (Zhou and Steffenson, 2013 ; Genievskaya et al, 2018 ), Europe (Xu et al, 2018 ), and India (Visioni et al, 2018 ), were used to identify the genetic architecture of complex traits (heading time, number of kernels per spike, grain yield) and disease resistance (durable spot, stripe rust) in barley. Although some studies used worldwide collections of barley germplasm, few have included barley varieties from Tibet (Pasam et al, 2012 ; Gyawali et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GWAS has proven to be very effective for capturing relevant marker-trait associations (MTAs) for yield components, results reported from studies in different regions of the world are revealing the tendency for a strong influence of the environmental conditions with significant genotype x environment interaction (GEI) revealed. For example, GWAS results obtained from multilocation studies related to the identification of QTLs for yield performance showed different responses, and QTLs for yield components were identified in different parts of the genome [16,17], similarly to what reported in common wheat [24,8] and barley [25,26,27]. Therefore, the success of regional projects largely relies on local GWA studies based on the evaluation of genetically diverse wild and domesticated germplasm.…”
Section: Introductionmentioning
confidence: 78%
“…Currently, the efficiency of breeding programs might be improved by the application of modern genomic technologies [12, 13], such as the automated genome-wide profiling of large collections based on the use of single nucleotide polymorphism (SNP) markers [14, 15, 16]. In barley, an Illumina-based SNP genotyping platform was extensively used for both the evaluation of wild [17, 18, 19] and cultivated barley accessions [20, 21, 22, 23]. The fast generation of large amounts of SNP genotyping data was particularly successful for the genetic mapping of quantitative trait loci (QTL) of agronomic traits based on genome-wide association study (GWAS).…”
Section: Introductionmentioning
confidence: 99%